2005
DOI: 10.1002/cbdv.200590048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Precursor of (S)-3-Methyl-3-sulfanylhexan-1-ol, the Sulfury Malodour of Human Axilla Sweat

Abstract: A careful study of human axillary microflora led us to the identification of a new strain of Staphylococcus haemolyticus. The role in axillary malodour formation of this microorganism was compared to those of Corynebacterium xerosis and Staphylococcus epidermidis, upon incubation on sterile human eccrine and apocrine axilla sweat. St. haemolyticus was responsible for the strongest sulfury malodour and the generation of the volatile sulfur compound (VSC) (S)-3-methyl-3-sulfanylhexan-1-ol (3). In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 18 publications
7
76
0
Order By: Relevance
“…We could detect cleavage of the Cys-Gly-(S) conjugate only in strains of Corynebacteria, which is in agreement with the well known fact that human subjects with a high population of Corynebacteria can form axillary malodor (2,25). However, Starkenmann et al (14) have reported that an isolate of S. haemeolyticus is releasing 3M3SH from the Cys-Gly-(S) conjugate. Thus, it appears that members of different bacterial genera present on axillary skin have adopted their enzymes to these secreted substrates.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We could detect cleavage of the Cys-Gly-(S) conjugate only in strains of Corynebacteria, which is in agreement with the well known fact that human subjects with a high population of Corynebacteria can form axillary malodor (2,25). However, Starkenmann et al (14) have reported that an isolate of S. haemeolyticus is releasing 3M3SH from the Cys-Gly-(S) conjugate. Thus, it appears that members of different bacterial genera present on axillary skin have adopted their enzymes to these secreted substrates.…”
Section: Discussionsupporting
confidence: 90%
“…However, the conjugate with the dipeptide Cys-Gly was later reported as the key precursor for 3M3SH (14). The presented LC-MS data now confirm the Cys-Gly-(S) conjugate as the major precursor of 3M3SH, but, in combination with the LC-MS 2 analysis, they clearly show that the Cys-(S) conjugate is also present, albeit at lower levels.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…On the other hand, the most powerful aroma molecules in nature are polyfunctional mercaptans, which are molecules combining a second chemical functionality in the molecule. Most of such polyfunctional mercaptans have very strong and distinctive smells and are responsible for the aroma and flavor of numerous vegetable species, such as box, blackcurrant, grapefruit [4], passion fruit [5,6], onions [7,8] and green tea [9], of some foods such as coffee [10,11], meat [12][13][14], Iberian ham [15] and wine [16][17][18][19] and even have been described as majorly responsible for the odor of some species of mammals such as skunks [20], cats [21] or even humans [22]. There is an obvious need for analytical strategies not only for their quantitative determination, but also for their selective isolation.…”
Section: Introductionmentioning
confidence: 99%